Gonorrhea testing, morbidity, and reporting using an integrated sexually transmitted disease registry in Indiana: 2004–2016. (January 2021) - Ojo, Opeyemi C; Arno, Janet N; Tao, Guoyu; Patel, Chirag G; Zhang, Zuoyi; Wang, Jane; Holderman, Justin; Dixon, Brian E
Surveillance of gonorrhea (GC), the second most common notifiable disease in the United States, depends on case reports. Population-level data that contain the number of individuals tested in addition to morbidity are lacking. We performed a cross-sectional analysis of data obtained from individuals tested for GC recorded in a sexually transmitted disease (STD) registry in the state of Indiana. Descriptive statistics were performed, and a Poisson generalized linear model was used to evaluate the number of individuals tested for GC and the positivity rate. GC cases from a subset of the registry were compared to CDC counts to determine the completeness of the registry. A total of 1, 870, 811 GC tests were linked to 627, 870 unique individuals. Individuals tested for GC increased from 54, 334 in 2004 to 269, 701 in 2016; likewise, GC cases increased from 2, 039 to 5, 997. However, positivity rate decreased from 3.75% in 2004 to 2.22% in 2016. The difference in the number of GC cases captured by the registry and those reported to the CDC was not statistically significant (P = 0.0665). Population-level data from an STD registry combining electronic medical records and public health case data may inform STD control efforts. In Indiana, increased testing rates appeared to correlate with increased GC morbidity.